POTENSI VEGETASI PAKAN DAN EFEKTIVITAS PERBAIKAN HABITAT RUSA TIMOR (Cervus timorensis, de Blainville 1822) DI TANJUNG PASIR TAMAN NASIONAL BALI BARAT - Burhanuddin Masy'ud; Indra Hadi Kusuma; Yandhi Rachmandani (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
The research was done to identified the diversities of food vegetation, food palatability, biomass, productivity and carraying capacity, and to know the effect of habitat improvement techniques (i.e burning, cutting and soil rotation) to growth of food vegetation of timor deer (Cervus timorensis) in Tanjung Pasir West Bali National Park. Ten plots sample (1 m2 per plot ) were used to study of vegetation diversities at two forest type (savanna and season forest). Food productivity were measured three times based on food vegetation age i.e 40 days, 30 and 20 days after cutting. Effect of treatment of habitat improvement technique to growth of vegetation was evaluated each week for 4 weeks by measure of the average of vegetation high gain. Result showed that there were 12 species of food vegetation of timor deer were found in Tanjung Pasir, 4 species (i.e. Imperata cylindrical, Vernonia cinerea, Eupatorium inulifolium and Lantana camara) were palatable (Index Palatability 0.34-0.66) and 5 species (Streblus asper, Azadirachta indica, Digitaria ciliaris, Shoutenia ovata, and Xanthophullym excelsum) were less palatable (Index Palatability < 0,33). Total productivity of food vegetationin of deer habitat in Tanjung Pasir Resort (+ 645 ha) were predicted about 40.17 kg/ha/day so that total carrying capacity of the area was about 324 deers. Proximate analysis were showed that timor deer food vegetation in this area was relatively good, showed by percentage of protein (4-22 %) and crud fiber (22-33%). Result of implementation of habitat improvement techniques showed that the burning technique was good effect to growth of food vegetation than the other techniques (cutting and soil rotation).Keywords: Timor deer, food vegetation potency, habitat improvement, burning technique, national park.